CLAYMOTION : "CERITA RAKYAT BATU MENANGIS DALAM FILM PENDIDIKAN UNTUK ANAK" - Nazari, Fahruzi (2017)
The formulation of the problem in this study is "How the results of making claymotion: Stone People's story crying in the film education for Children". This study aims to produce folklore claymotion about Crying Stone people's story to be applied into SBK learning, as penujuang process of learning in class 4 SDN 16 South Pontianak. The method used in this research is descriptive because it aims to make the planning systematically, factually and accurately about the facts and the nature of the polution. The population in this research are 6 people consisting of (2 graphic designer, 2 graduate student of education, 2 art students and 2 clay craftsmen) and 4A, 4B, 69 students and 1 elementary school teacher. The results of this study consisted of the results of making claymotion media as a medium of learning including both categories, and the results of student learning grade 4A with an average value of 78.3. Based on the results of research and conclusions then researchers can suggest as follows: a. In making claymotion media to look more alive using property that support. b. In preparing the learning media teachers are expected to try to make their own videos. c. Teachers should try their best to be skilled at designing the lesson plans of RPP. d. In the implementation of learning teachers are expected not to dominate learning activities, such as using lecture methods. e. In order for learners to get the value of the maximum learning outcomes, teachers should use learning media that can attract student learning interests. ----- Adapun rumusan masalah dalam penelitian ini adalah "Bagaimanakah hasil pembuatan claymotion : cerita Rakyat Batu menangis dalam film pendidikan untuk Anak". Penelitian ini bertujuan untuk menghasilkan folklore claymotion tentang cerita rakyat Batu Menangis untuk dapat diaplikasikan ke dalam pembelajaran SBK, sebagai penujuang proses pembelajaran di kelas 4 SDN 16 Pontianak Selatan. Metode yang digunakan dalam penelitian ini adalah deskriptif karena bertujuan untuk membuat perencanaan secara sistematis, faktual dan akurat mengenai fakta - fakta dan sifat - sifat polulasi. Populasi dalam penelitian ini adalah 6orang narasumber yang terdiri dari (2 orang desainer grafis, mahasiswa S2 Pendidikan 2 orang Seni Rupa dan 2 orang pengrajin clay) dan peserta didik kelas 4A, 4B yang berjumlah 69 orang dan 1 orang guru SD. Adapun hasil penelitian ini terdiri dari hasil pembuatan media claymotion sebagai media pembelajaran termasuk kategori baik, dan hasil belajar siswa kelas 4A dengan nilai rata - rata 78,3. Berdasarkan hasil penelitian dan kesimpulan maka dapat peneliti sarankan sebagai berikut : a. Dalam membuat media claymotion agar terlihat lebih hidup menggunakan property yang menunjang. b. Dalam menyiapkan media pembelajaran guru diharapkan berusaha membuat video sendiri. c.Guru hendaknya berusaha maksimal supaya terampil merancang rencana pelaksanaan pembelajaran RPP. d. Dalam pelaksanaan pembelajaran guru diharapkan tidak mendominasi kegiatan pembelajaran, misalnya menggunakan metode ceramah. e. Agar peserta didik memperoleh nilai hasil belajar yang maksimal, hendaknya guru menggunakan media pembelajaran yang dapat menarik minat belajar siswa.